Determine the Solution of Delay Differential Equations using Runge-Kutta Methods with Cubic-Spline Interpolation - Agus Dahlia; Rahma Qudsi ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2023)
This paper describes some iterations for term delay in Delay Differential Equation (DDE), which is causing a huge number of iteration calculations. Time-delay was approximated using Cubic-Spline Interpolation, so DDE can rewrite as Differential Equations. Then, Runge-Kutta methods have been used to determine the solution of Differential equations from DDE.